Inverse Relationship of Blood Pressure to Long-Term Outcomes and Benefit of Cardiac Resynchronization Therapy in Patients With Mild Heart Failure. (September 2015) - Biton, Yitschak; Moss, Arthur J.; Kutyifa, Valentina; Mathias, Andrew; Sherazi, Saadia; Zareba, Wojciech; McNitt, Scott; Polonsky, Bronislava; Barsheshet, Alon; Brown, Mary W.; Goldenberg, Ilan
<x xml:space="preserve">Abstract</x> Background— Previous studies have shown that low blood pressure is associated with increased mortality and heart failure (HF) in patients with left ventricular dysfunction. Cardiac resynchronization therapy (CRT) was shown to increase systolic blood pressure (SBP). Therefore, we hypothesized that treatment with CRT would provide incremental benefit in patients with lower SBP values. Methods and Results— The independent contribution of SBP to outcome was analyzed in 1267 patients with left bundle brunch block enrolled in Multicenter Automatic Defibrillator Implantation Trial With Cardiac Resynchronization Therapy (MADIT-CRT). SBP was assessed as continuous measures and further categorized into approximate quintiles. The risk of long-term HF or death and CRT with defibrillator versus implantable cardioverter defibrillator benefit was assessed in multivariate Cox proportional hazards regression models. Multivariate analysis showed that in the implantable cardioverter defibrillator arm, each 10-mm Hg decrement of SBP was independently associated with a significant 21% (P<0.001) increased risk for HF or death, and patients with lower quintile SBP (<110 mm Hg) experienced a corresponding >2-fold risk-increase. CRT with defibrillator provided the greatest HF or mortality risk reduction in patients with SBP<110 mm Hg hazard ratio of 0.34, P<0.001, when compared with hazard ratio of 0.52, P<0.001, in those with 110>SBP≥136 mm Hg and hazard ratio of 0.94, P=0.808, with SBP>136 mm Hg (P for trend=0.001). Conclusions— In patients with mild HF, prolonged QRS, and left bundle brunch block, low SBP is related to higher risk of mortality or HF with implantable cardioverter defibrillator therapy alone. Treatment with CRT is associated with incremental clinical benefits in patients with lower baseline SBP values. Clinical Trial Registration— URL: http://www.clinicaltrials.gov. Unique identifier: NCT00180271.